Instructing Adults, Attracting Children: Toy Displays in Republican China - Valentina Boretti (Strenae)
From the early twentieth century, a discourse developed in China whereby children were assets for national rejuvenation, and toys were crucial to shaping them. The relevance of childhood and toys was however also deployed to tutor adults: the present article uses toy displays as an entry point to analyse this question. Discussing exhibitions staged by educational and governmental agencies in the 1920s and 1930s, it examines efforts to shift the perception of playthings from gadgets to essential formative tools that could not be manufactured, acquired or used casually. Not only were exhibitions a way to disseminate the discourse of toys as symbols and agents of improvement, but also they served to teach expert-defined competence to adults, most notably producers and parents.